Analisis Komponen Evaluasi Pembelajaran pada Modul Ajar Guru PAI di SMK Negeri 1 Sei Suka - Laila Fathimah; Nurmawati Nurmawati; Yusranida Hidayati; Ilham Putra Pratama; Muhammad Sofwan (Lembaga Yasin AlSys, 2026)
Although the evaluation of Islamic Religious Education (PAI) learning has received attention in previous studies, research that specifically investigates the completeness and quality of evaluation components in Kurikulum Merdeka-based PAI teaching modules at the vocational high school level remains limited. This study aimed to analyze the completeness, appropriateness, and quality of learning evaluation components in PAI teaching modules developed by teachers at SMK Negeri 1 Sei Suka. A qualitative approach was employed using a case study design grounded in document analysis, involving 3–4 PAI teachers selected through purposive sampling. Data were collected through document analysis of PAI teaching modules and semi-structured interviews, and were then analyzed using content analysis and thematic analysis. The findings indicate that the PAI teaching modules generally include diagnostic, formative, and summative assessments and, for the most part, align with the principles of authentic assessment in Kurikulum Merdeka. However, variations in quality were still identified, particularly in the clarity of rubrics for assessing attitudes, the accuracy of assessment indicators, and the systematization of follow-up learning programs in the form of remedial and enrichment activities. These findings contribute to the development of learning evaluation theory and authentic assessment in Islamic education and broaden the understanding of PAI learning evaluation practices in vocational high schools. The study concludes that the systematic, measurable, and authentic development of learning evaluation components plays an important role in improving the quality of PAI instruction and recommends sustained support for teachers through training and mentoring in assessment development. The implications of this study include theoretical contributions to enriching the literature on PAI learning evaluation and practical implications for schools and teacher professional development, while also opening up opportunities for further research on the influence of evaluation quality on student learning outcomes and character formation.